Obstetric Care For Primigravida Mothers With Antepartum Depression Before Delivery At Pratama Siti Kholijah Clinic Jl. Marelan I, Terjun, Kec. Medan Marelan - Fauza, Rahmawani; Rambe, Nova Linda (CV. Devitara, 2023)
Antepartum depression or stress is a complication of pregnancy risks and negative experiences in a woman's life. According to a systematic review, the incidence of mental health disorders such as depression and anxiety disorders in mothers in developing countries was recorded to have an average of 15.6% during pregnancy and 19.8% after delivery. A study showed the prevalence of antepartum depression, amounting to 26.6%. Depression during pregnancy has been shown to produce unwanted perinatal eg preterm delivery, low birth weight, preeclampsia, low Apgar scores at 1 and 5 minutes. The adrenal cortex secretes cortisol in response to ACTH, diurnal rhythms, and stress. Guided imagery relaxation techniques using soothing words and sounds; directs the user to imagine a psychological or physiological state in a relaxed manner. Researchers provide comprehensive midwifery care for pregnant women, maternity, postpartum, BBL, neonates and family planning using a midwifery management approach to Mrs